[A wooden hut] - (:unkn) unknown (My University, 2010)
A wooden hut with a thatched roof on the banks of a river nestled among the coconut trees.
Colour:Black and white; Style:Landscape; Other:Bordered,Undivided
Keywords: Trinidad and Tobago; Postcards; Huts; Wooden-frame houses; Coconut palm